2020
DOI: 10.24235/al.ibtida.snj.v7i2.6836
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Strategies in Developing and Measuring Students’ Communication Skills

Abstract: A good communication skill is one of the capabilities that must be mastered by students to be able to socialize, adapt, and compete with others in the scope of school and social life in the 21st century. The purpose of this type of descriptive qualitative research was about to describe the teachers' strategies in developing and conducting an assessment related to the communication skills of elementary school students in Indonesia. Data were obtained through interviews with 10 elementary school teachers in Yogy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…S. Chang et al, 2014;Diningrat et al, 2020;Noer et al, 2021;Octaberlina & Muslimin, 2020). Furthermore, discussions held in class became more limited during the Covid-19 pandemic, even though previous research has shown that learning by discussion is an effective strategy in developing students' communication skills (Rosdianti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…S. Chang et al, 2014;Diningrat et al, 2020;Noer et al, 2021;Octaberlina & Muslimin, 2020). Furthermore, discussions held in class became more limited during the Covid-19 pandemic, even though previous research has shown that learning by discussion is an effective strategy in developing students' communication skills (Rosdianti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Keterampilan komunikasi adalah salah satu kompetensi terpenting bagi warga dunia abad 21 (Chung et al, 2016). Kemampuan berkomunikasi baik secara verbal maupun nonverbal dapat memengaruhi keberhasilan seseorang atau kegagalan dalam mencapai tujuan, termasuk dalam hal pekerjaan atau menjalin hubungan dengan yang lain (Rosdianti et al, 2020). Kesalahan dalam berkomunikasi bisa berakibat buruk terhadap pemahaman, bahkan perdamaian.…”
Section: B Penerapan Keterampilan Berkomunikasiunclassified